Державна підтримка культурної діяльності української діаспори як напрям діаспоральної політики України - Тронь, А. (Народна творчість та етнологія, 2022)
Стаття присвячена аналізу законодавчої бази діаспоральної політики України, зокрема щодо задоволення національно-культурних потреб закордонних українців. Досліджується процес організації управління сферою відносин з українською діаспорою на рівні центральних органів виконавчої влади та відповідних дорадчо-консультативних інституцій, починаючи з 1991 року й до сьогодні. Специфіка співпраці України з діаспорою в галузі культури аналізується в контексті реалізації державних цільових програм співробітництва із закордонними українцями та культурної дипломатії. Ukrainian diaspora, especially the organizations of foreign Ukrainians in Western countries, has been of great importance in the processes of Ukrainian state-building from the time of Ukraine’s independence proclamation. Interaction with the diaspora and support for Ukrainians who have found themselves outside their homeland for various reasons are considered both a moral duty of the newly emerged Ukrainian state, but also a significant resource for the promotion of Ukrainian interests in the world and the development of state institutions within the country. Despite the obvious importance and relevance of this problem hitherto the issue of the state's significance in the cultural life of foreign Ukrainians has not been reflected in the historiography completely. The article is aimed at a comprehensive study of the diaspora policy of Ukraine in the cultural and educational sphere, its normative and legal basis, and specific features of the implementation of the state programs of cooperation with foreign Ukrainians concerning the assistance of their cultural activities. The source base of the study consists of normative and legal acts, analytical materials, reports on the implementation of the passports of budget programs, and other documents. It is established that the state programs, providing support to the Ukrainian diaspora in the 1990s and early 2000s are mostly declaratory. The approval of the National Concept of Cooperation with Ukrainians Abroad has become an important step in the context of the establishment of Cultural and Information Centers in the structure of foreign diplomatic missions of Ukraine in 2006, the expansion of the mandates of the Ministry of Foreign Affairs in the area of contacts with Ukrainians abroad, as well as more sufficient financial support of the relevant cooperation programs. Special attention is paid to the measures of cultural diplomacy development in 2015–2017. Conducted analysis of the current condition of diaspora policy of Ukraine proves that state support of the ethnic identity, and national and cultural originality of the Ukrainians abroad through educational programs, cultural projects, and information resources, is an important aspect of foreign policy of the newly founded Ukrainian state. Such actions have achieved some positive results, in particular in such areas as the preservation of Ukrainian traditional cultural heritage, scientific exchange, educational activities, and memory policy. However, recent political events in the world have shown that the efficiency of the use of connections with the diaspora and cultural diplomacy, in particular as to the counteraction to Russian propaganda and subversive policy is far from optimal. Implementation of state-initiated actions supporting the cultural activities of foreign Ukrainians can and should become one of the key factors of Ukraine’s international image guarantee in the future.